2018
DOI: 10.1155/2018/7285849
|View full text |Cite
|
Sign up to set email alerts
|

The III–V Triple-Junction Solar Cell Characteristics and Optimization with a Fresnel Lens Concentrator

Abstract: At present, the Fresnel lens are commonly used as the condenser in high-concentrating photovoltaic (HCPV) modules. It is ideally believed that the output power of a III-V triple-junction solar cell which is placed on the focal plane of a Fresnel lens is the largest, because the intensity of the sunlight on the focal plane is the largest. Actually, according to our work, the dispersion of sunlight through a Fresnel lens and the nonparallelism and divergence of the incident light will lead to changes in the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Through selective absorption of different regions of the solar spectrum, MJ solar cells achieve effective enhancement in conversion efficiency [1,5,6]. Currently, III-V compound materials are considered ideal for MJ solar cells [7,8]. Relevant literature has demonstrated that MJ solar cells fabricated from III-V compound materials have achieved a conversion efficiency of up to 46% under high solar concentration [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Through selective absorption of different regions of the solar spectrum, MJ solar cells achieve effective enhancement in conversion efficiency [1,5,6]. Currently, III-V compound materials are considered ideal for MJ solar cells [7,8]. Relevant literature has demonstrated that MJ solar cells fabricated from III-V compound materials have achieved a conversion efficiency of up to 46% under high solar concentration [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a surge in the development, manufacturing, and use of multi-junction solar cells all throughout. But, there were obstacles such as composition, overall size, and lattice matching of different junctions which have now almost been overcome by the use of transparent and conductive buffer layers or tunnel junctions [2][3][4][5][6]. Usually, an III-V multi-junction solar cell has been used as GaAs, InGaAs; InGaP....The 3J solar cells are used due to the ease of growth.…”
Section: Introductionmentioning
confidence: 99%
“…A number of Multi-junction thin film, and Si structures have been proposed. There are 5junction cells such as AlGaInP/ AlGaInAs/GaInAs/GaInNAs/Ge solar cells which result in a decent efficiency but are difficult to fabricate due to lattice mismatching and therefore need more tunnel junctions and buffer layers that lead to a higher number of trap levels and growth defects which lead to higher unwanted recombination [2,[7][8][9][10][11]. The non-radiative recombination causes the lattice to heat up which is unwanted.…”
Section: Introductionmentioning
confidence: 99%
“…Each sub-cell is designed to respond in a specific part of the solar spectrum. This concept was found to be the only one that was successfully commercialized among the other ways of high efficiency designs [5][6].…”
Section: Introductionmentioning
confidence: 99%